2021
DOI: 10.26855/ijfsa.2021.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Extension Demonstration of Improved Maize Technology at Midland Districts of Guji Zone, Southern Oromia, Ethiopia

Abstract: Participatory demonstration of improved maize technologies was conducted in two potential midland districts of Guji Zone in 2019. The main objective of the study was to popularize improved maize variety at midlands of Guji Zone. Two districts were selected based on their potential to grow maize and two peasant associations from each district were selected based on their accessibility. Fifteen farmers of gender inclusive were established as Farmers Research Group (FRG) at each peasant association. Three hosting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
3
0
0
Order By: Relevance
“…As a result, Kulani gave the highest yield followed by Gibe-2 while the local variety gave a lower yield compared to both improved maize varieties. This study is consistent with the findings of [11] and [12] who found that improved varieties were significantly higher yielders compared to local checks.…”
Section: Yield Performance Of the Demonstrated Varietiessupporting
confidence: 92%
See 2 more Smart Citations
“…As a result, Kulani gave the highest yield followed by Gibe-2 while the local variety gave a lower yield compared to both improved maize varieties. This study is consistent with the findings of [11] and [12] who found that improved varieties were significantly higher yielders compared to local checks.…”
Section: Yield Performance Of the Demonstrated Varietiessupporting
confidence: 92%
“…The calculated technology index percentage of yield advantage of the two OPV (Kulani and Gibe-2) maize varieties showed that they have 73.3 and 65.2% yield advantage over the local variety, respectively (Table 3). This study is similar to the previous findings of [11] and [12] who reported that an improved maize variety had more yield advantage over the local check. Production costs and return from improved OPV maize production were calculated by deducting total cost from total revenue.…”
Section: Yield Advantage Of the Two Opv Maize Varieties Over The Loca...supporting
confidence: 92%
See 1 more Smart Citation
“…to grow productive food plants, such as maize. In the world, the area of maize and its yield are increasing [1] - [4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the productivity of plants, it is necessary to apply the latest, improved, scientifically based technological elements, such as mineral fertilizers, hybrids, high-quality seed material, etc. [1]- [2], [4] - [9].…”
Section: Introductionmentioning
confidence: 99%